2020
DOI: 10.3390/molecules25122809
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Ginsenoside Composition in the Creation of Black Ginseng Leaf

Abstract: Ginseng is an increasingly popular ingredient in supplements for healthcare products and traditional medicine. Heat-processed ginsengs, such as red ginseng or black ginseng, are regarded as more valuable for medicinal use when compared to white ginseng due to some unique less polar ginsenosides that are produced during heat-treatment. Although ginseng leaf contains abundant ginsenosides, attention has mostly focused on ginseng root; relatively few publications have focused on ginseng leaf. Raw ginseng leaf was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
(53 reference statements)
1
19
0
Order By: Relevance
“…These results indicate that both the temperature and time of FIR treatment are important factors affecting ginsenoside variation in ginseng leaves. In addition, Chen et al [ 36 ] reported that polar PPD-type ginsenosides (Rb1, Rb2, Rb3, Rc, and Rd) can be converted to Rg3, F2, Rh2, C-K, PPD, and Rk2 during the creation of black ginseng leaves. Thus, it is important to select suitable processing methods in consideration of the final products before processing ginseng leaves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that both the temperature and time of FIR treatment are important factors affecting ginsenoside variation in ginseng leaves. In addition, Chen et al [ 36 ] reported that polar PPD-type ginsenosides (Rb1, Rb2, Rb3, Rc, and Rd) can be converted to Rg3, F2, Rh2, C-K, PPD, and Rk2 during the creation of black ginseng leaves. Thus, it is important to select suitable processing methods in consideration of the final products before processing ginseng leaves.…”
Section: Resultsmentioning
confidence: 99%
“…They showed the variation in Rg1, Rh1, Rh4, and Rk3 in white ginseng heated at different temperatures at 20 MPa for 2 h. In our results, relatively higher amounts of F4 and Rg6 were transformed compared to Rh4 and Rk3. Differently, Chen et al [ 36 ] investigated ginsenoside changes in black ginseng leaf products and suggested that the degradation of Re and Rg1 to minor ginsenosides, such as Rk3, Rh4, and PPT, is the main transforming PPT-type pattern. This can be explained by the different progressions of thermal processing (methods, time, temperature, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…The different ginseng extracts (TGE, HPG, LPG, and NGE) and twenty-one ginsenoside reference standards were prepared about 1 mg/mL using deionized water or 70% methanol, and then filtered through a 0.22-mm syringe filter before HPLC injection. The HPLC analysis, including validated calibration curves, was conducted as a previous study [ 42 ]. The HPLC instrument used in this study was a Shimadzu Prominence LC-20A UFLC Stack HPLC system (Shimadzu, Kyoto, Japan) equipped with a DGU-20A3 degasser, LC-20AD pump, CTO column oven, SPD-20A detector, and SIL-20A autosampler.…”
Section: Methodsmentioning
confidence: 99%
“…Ginseng, including P. ginseng (comprising the root, 35,36,200,294–298 leaf, 299 and berry 300 ), P. quinquefolius , 301,302 P. notoginseng , 28,303,304 and P. vietnamensis , 305 can be prepared by various processing technologies ( e.g. repetitious steaming, fermentation, chemical processing, baking, and gamma-ray irradiation, etc. )…”
Section: Quality Controlmentioning
confidence: 99%